Teacher Strategies for Fostering Fifth-Grade Students’ Learning Interest in Pancasila Education - Niluh Putu Feni Sri Lestari; La Sisi; Erwin Eka Saputra (Journal of Education and Learning Sciences, 2025)
Interest in learning is an important factor influencing the success of the learning process in elementary education. Students with a strong interest in learning tend to demonstrate greater attention, enthusiasm, active participation, and willingness to engage with learning materials. Preliminary observations indicated that fifth-grade students' interest in learning Pancasila Education was relatively low, as reflected in limited attention during lessons, low participation in classroom activities, and the limited variation of instructional strategies implemented by the teacher. This study aimed to describe the strategies used by the teacher to enhance fifth-grade students' interest in learning Pancasila Education. A qualitative approach with a descriptive design was employed. Data were collected through observation, semi-structured interviews, and documentation involving the school principal, the fifth-grade teacher, and fifth-grade students as informants. Data were analyzed using Miles and Huberman's interactive model, which comprises data reduction, data display, and conclusion drawing and verification. The findings showed that the teacher implemented varied instructional strategies, including lectures, discussions, question-and-answer activities, educational games, the use of pictures and videos, motivational support, communicative interaction, and contextual learning. These strategies contributed to increased student attention, enthusiasm, active participation, and involvement throughout the learning process. The findings indicate that the consistent implementation of varied, interactive, communicative, and contextual instructional strategies plays an important role in enhancing students' interest in learning Pancasila Education at the elementary school level.